2022
DOI: 10.1101/2022.09.23.509131
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multisensory inputs control the regulation of time investment for mating by sexual experience in male Drosophila melanogaster

Abstract: Males have finite resources to spend on reproduction. Thus, males rely on a 'time investment strategy' to maximize their reproductive success. For example, male Drosophila melanogaster extends their mating duration when surrounded by conditions enriched with rivals. Here we report a novel form of behavioral plasticity whereby male fruit flies exhibit a shortened duration of mating when they are sexually experienced; we refer to this plasticity as 'shorter-mating-duration (SMD)'. SMD is a plastic behavior and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…Using both theoretical and empirical approaches, we further showed that SMD represents the adaptive behavioral plasticity of male flies (Fig 11). Previous research by our group and others demonstrated that past exposure to rivals lengthens mating duration, a characteristic known as longer-mating-duration (LMD) [14][15][16][17][18][19][20][21][22][23]76]. The two behavioral circuits for LMD and SMD might have evolved independently since they use different sensory cues for detecting 'rivals' or 'females' for 'sexual competition' or 'mating investment', respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Using both theoretical and empirical approaches, we further showed that SMD represents the adaptive behavioral plasticity of male flies (Fig 11). Previous research by our group and others demonstrated that past exposure to rivals lengthens mating duration, a characteristic known as longer-mating-duration (LMD) [14][15][16][17][18][19][20][21][22][23]76]. The two behavioral circuits for LMD and SMD might have evolved independently since they use different sensory cues for detecting 'rivals' or 'females' for 'sexual competition' or 'mating investment', respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This behavior is believed to be an adaptation that allows male flies to conserve energy by mating quickly then continuing to other activities (Supplementary information, Fig. S1B) [45][46][47][48] .…”
Section: Resultsmentioning
confidence: 99%
“…TRIC serves as a valuable complement to functional Ca 2+ imaging by integrating long-term changes in neuronal activity and providing genetic access to neurons based on their activity. Given that both LMD and SMD require at least 6-12 hours of social isolation or sexual interaction 71,72 , repeated sensory inputs could potentially lead to the accumulation of the modified transcription factor within the nucleus of activated neurons in vivo . Indeed, social isolation or sexual experiences affected the neural activity of GAL4 SIFa-PT -labeled neurons (Fig.…”
Section: Resultsmentioning
confidence: 99%